Rhizobium Inoculation Enhances the Resistance of Alfalfa and Microbial Characteristics in Copper-Contaminated Soil - Duan, Chengjiao; Mei, Yuxia; Wang, Qiang; Wang, Yuhan; Li, Qi; Hong, Maojun; Hu, Sheng; Li, Shiqing; Fang, Linchuan (Frontiers in Microbiology, 2022)
Some studies have reported the importance of rhizobium in mitigating heavy metal toxicity, however, the regulatory mechanism of the alfalfa-rhizobium symbiosis to resist copper (Cu) stress in the plant-soil system through biochemical reactions is still unclear. This study assessed the effects of rhizobium (Sinorhizobium meliloti CCNWSX0020) inoculation on the growth of alfalfa and soil microbial characteristics under Cu-stress. Further, we determined the regulatory mechanism of rhizobium inoculation to alleviate Cu-stress in alfalfa through plant-soil system. The results showed that rhizobium inoculation markedly alleviated Cu-induced growth inhibition in alfalfa by increasing the chlorophyll content, height, and biomass, in addition to nitrogen and phosphorus contents. Furthermore, rhizobium application alleviated Cu-induced phytotoxicity by increasing the antioxidant enzyme activities and soluble protein content in tissues, and inhibiting the lipid peroxidation levels (i.e., malondialdehyde content). In addition, rhizobium inoculation improved soil nutrient cycling, which increased soil enzyme activities (i.e., β-glucosidase activity and alkaline phosphatase) and microbial biomass nitrogen. Both Pearson correlation coefficient analysis and partial least squares path modeling (PLS-PM) identified that the interactions between soil nutrient content, enzyme activity, microbial biomass, plant antioxidant enzymes, and oxidative damage could jointly regulate plant growth. This study provides comprehensive insights into the mechanism of action of the legume-rhizobium symbiotic system to mitigate Cu stress and provide an efficient strategy for phytoremediation of Cu-contaminated soils.